Checking the possibility of controlling fuel element by X-ray computerized tomography; Journal of Physics: Conference Series; Vol. 881 : Innovations in Non-Destructive Testing (SibTest 2017) - Trinh V. B.; Zhong Y.; Osipov S. P. Sergey Pavlovich; Batranin A. V. Andrey Viktorovich (2017, 2017)
Title screen